Fingerprinting of falsified artemisinin combination therapies via direct analysis in real time coupled to a compact single quadrupole mass spectrometer. Issue 36 (15th July 2016) - Bernier, Matthew C.; Li, Frederick; Musselman, Brian; Newton, Paul N.; Fernández, Facundo M.
Abstract : Using portable single-quadrupole DART-MS technology, suspect pharmaceuticals can be rapidly and efficiently analyzed providing detailed information on their true origin. Abstract : Falsified anti-malarial treatments continue to constitute a major health crisis, especially in malarious Africa. Even after detection of poor quality pharmaceuticals, it is critical that they be fully analyzed to determine their components, in order to assess their health effects and ultimately allow forensic tracing of their sources of production and distribution. Timely assessment requires robust and complete field-testing, or at the very least timely analysis after seizure or purchase. Ideally, low-cost and simple analytical equipment such as portable mass spectrometry (MS) is the best approach for achieving this quick and informative analysis. To date, Direct Analysis in Real Time (DART) MS has been successfully implemented to rapidly analyze falsified artemisinin-based combination therapies (ACTs) in laboratory settings, but this approach typically translates into high-cost and the need for high-resolution instrumentation. Here, we examine the use of DART ionization coupled with a portable low-resolution single-quadrupole instrument, and compare its success in fingerprinting anti-malarial tablets with higher resolution instrumentation. Using single quadrupole DART-MS, the same sample components were detected as with the high-resolution instrument, while needing significantly less consumables and power, and the additional advantages of increased portability and ease of use. Using Principal Component Analysis (PCA) of DART data, specific classes of falsified ACTs were identified, providing a more straightforward method for sourcing counterfeits and assessing their similarities.